Implementasi Restorative Justice dalam Reformasi Sistem Peradilan Pidana Indonesia - Khoirul Anwar Dalimunthe; Muhammad Wirdan; Asmak Ul Hosnah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This paper discusses the implementation of restorative justice in the reform of Indonesia’s criminal justice system. Restorative justice offers a new approach that differs from traditional punishment-based systems, focusing on repairing harm, reconciliation, and healing between offenders, victims, and the community. In the context of Indonesian criminal law, there has been a shift from emphasizing imprisonment as the main form of punishment to creating solutions that are fair and beneficial to all parties involved. Restorative justice is primarily applied in minor offenses and cases involving children, through mediation, compensation, and community service. Legal support has been provided through Police Regulation No. 6 of 2019 and the Attorney General’s Regulation No. 15 of 2020. However, the implementation of restorative justice faces challenges such as differences in procedure between legal institutions, lack of universal regulations, and a prevailing mindset among the public and law enforcement officers regarding retributive justice. The paper concludes that the reform of Indonesia’s criminal law through restorative justice can provide significant benefits such as victim recovery, reduced recidivism, and strengthened social relationships. However, this requires commitment, collaboration, and professionalism from all parties to ensure the system is truly focused on healing and substantive justice.